Genome-wide identification and expression analysis of the VQ gene family in Cicer arietinum and Medicago truncatula - Lei Ling; Yue Qu; Jintao Zhu; Dan Wang; Changhong Guo (PeerJ, 2020)
Valine-glutamine (VQ) proteins are plant-specific proteins that play crucial roles in plant development as well as biotic and abiotic stress responses. VQ genes have been identified in various plants; however, there are no systematic reports in Cicer arietinum or Medicago truncatula. Herein, we identified 19 and 32 VQ genes in C. arietinum and M. truncatula, respectively. A total of these VQ genes were divided into eight groups (I–VIII) based on phylogenetic analysis. Gene structure analyses and motif patterns revealed that these VQ genes might have originated from a common ancestor. In silico analyses demonstrated that these VQ genes were expressed in different tissues. qRT-PCR analysis indicated that the VQ genes were differentially regulated during multiple abiotic stresses. This report presents the first systematic analysis of VQ genes from C. arietinum and M. truncatula and provides a solid foundation for further research of the specific functions of VQ proteins.